2021
DOI: 10.1021/acs.jced.1c00672
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Measurement and Data Correlation of Pyrimethamine in 13 Pure Solvents at Temperatures from 278.15 to 318.15 K

Abstract: The solubility of PMN in 13 organic solvents (methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, isobutanol, acetone, acetonitrile, methyl acetate, ethyl acetate, n-propyl acetate, and isopropyl acetate) was determined by the gravimetric method over the temperatures ranging from 278.15 to 318.15 K at 0.1 MPa. The solubility of all selected solvents increases with increasing temperature; however, the change in methanol is substantially more than that in other solvents. Four models, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…In order to verify the accuracy of the experiment, the solubility data of fluorene in methanol, ethanol, isopropyl alcohol, and n-propanol and in the paper were compared with the solubility data of the existing literature in Figures S2− S5. [7][8][9]13 The result shows that the experimental solubility is consistent with ref 9 but has some differences from the solubility data of fluorene in ref 7, ref 8, and ref 13, The main reason is likely the different determination methods. Additionally, we measured the solubility of fluorene by HPLC analysis compared with the solubility determined by the gravimetry method.…”
Section: Solubility Measurementssupporting
confidence: 75%
See 1 more Smart Citation
“…In order to verify the accuracy of the experiment, the solubility data of fluorene in methanol, ethanol, isopropyl alcohol, and n-propanol and in the paper were compared with the solubility data of the existing literature in Figures S2− S5. [7][8][9]13 The result shows that the experimental solubility is consistent with ref 9 but has some differences from the solubility data of fluorene in ref 7, ref 8, and ref 13, The main reason is likely the different determination methods. Additionally, we measured the solubility of fluorene by HPLC analysis compared with the solubility determined by the gravimetry method.…”
Section: Solubility Measurementssupporting
confidence: 75%
“…The PXRD patterns of the raw material of fluorene and the solid residues in the six binary solvents are presented in Figure 2, which corresponds to the report in the literature. 9 It can be observed that the characteristic peaks of fluorene in the selected solvents had no change compared to that of the raw material, which indicates that no polymorphic transformation of fluorene appeared in the experimental process. 26,27 3.2.…”
Section: Resultsmentioning
confidence: 89%